Athletes’ pride bridge: Network centrality analysis to clarify the societal values of sports after the 2011 disaster in Japan - Sasaki, Koh (Advances in Social Sciences Research Journal, 2019)
This reseach builds on our previous study, examining recognition of social management and observes the interpretation of benevolent sports activities following Japan’s 2011 earthquake and tsunami. After the incident, most sports and recreational activities were suspended; however, various benevolent sports activities were arranged to benefit the damaged areas. This study investigates the recognised human value structure of sports in situation of great public anxiety by applying the life management concepts of time perspective and hope. The results regarding the terminal values study suggest the greatest recognition of ‘hope for the future’, ‘family bonds’, ‘excellence’, global concern’ and ‘life force’. Furthermore, the instrumental values study suggests greatest recognition of the ‘ambitious’, ‘courageous’, ‘self-reliant’, ‘competent’ and ‘respectful’ that indicate concern for inner motivation and survival capability. Network analysis (graph theory and centering resonance analysis) presents as holistic evaluation method for the positional functions of societal values and organization. Lonely coaches and athletes could be supported by some social pride for their long term struggle for training under heavy pressure. Purely following the goal is a kind of heterogeneous and unique in a good sense. However, its mind is to co-evolve community and social philosophy. The originality may exert the power to connect society with intense change, high uncertainty, complex era. The value of sport life force means an extremely tactile information and create a direct communication community in the so-called information society.